Tetralogy of Fallot whit a “contralateral” ductus arteriosus - Careddu, Lucio; Petridis, Francesco D; Angeli, Emanuela; Romano, Giorgio; Donti, Andrea; Gargiulo, Gaetano D (Acta Biomedica Atenei Parmensis, 2019)
Two neonates were taken shortly after birth to our unit with a prenatal diagnosis of [S,D,S] Tetralogy of Fallot with pulmonary atresia and “unusual” aorta to pulmonary connection. The echocardiogram confirmed the main diagnosis showing: a left aortic arch with a vascular connection between the right innominate artery and the origin of the right pulmonary artery in patient A; and right aortic arch with a vascular connection between the left innominate artery and the origin of the left pulmonary artery in patient B.